Upacara Su’u Ine Mbupu Wangga Ame Uwa di Komunitas Adat Wodowatu - Asthincya Goo, Maria; Suarsana, I Nyoman; Sama, I Nyoman (Sunari Penjor : Journal of Anthropology; Vol 3 No 2 (2019), 2021)
The Su’u ine mbupu wangga ame uwa  ceremony held by the Wodowatu indigenous community of Keo Tengah, Nagekeo Regency, NTT Province is a very rare ceremony to be held. The Su’u ine mbupu wangga ame uwa  ceremony involves five tribes in its process, which consists of believer of Catholic and Islam. This ceremony is believed by the adat community of Wodowatu to have a very important function for their survival. This research aimed to reveal the process and function of the Su’u ine mbupu wangga ame uwa  ceremony. The functionalism theory by Merton. The concepts used are Function, Ceremony, and Society. The study research methods with Ethnographic research model through observation technic, interview, and literature studies. Supporting intruments of this research are interview guides, voice recorders, camera, and stationery.Based on the results of the study, it is known that the ceremony of Su’u ine mbupu wangga ame uwa  has three important stages, namely the first stage or the preparation stage which consist of internal deliberations between the Adat leaders of Sa’o Mere and Doka Ora; The second stage is the implementation stage which consist the preparation of materials, the stage of processing. The third stage, the final stage, consists of, traditional party, and the tolak bala rituals. Su’u ine mbupu wangga ame uwa  also has functions that is known and also unknown to their indigenous community such as religious function, educational function, kinship function, and economic function.